RANDOM FOREST MODEL TO PREDICT THE HEIGHT OF EUCALYPTUS - Lima, Elizeu de S.; Souza, Zigomar M. de; Oliveira, Stanley R. de M.; Montanari, Rafael [UNESP]; Farhate, Camila V. V. [UNESP] (Soc Brasil Engenharia Agricola, 2022)
Eucalyptus (Eucalyptus urograndis) production has significantly advanced over the past few years in Brazil, especially with regard to acreage and productivity. Machine learning has made significant advances in most varied fields of agrarian sciences. In this context, this study aimed to use physicochemical variables of the soil as well as climatic and dendrometric variables of eucalyptus to predict its height using the random forest algorithm. The study was conducted in the municipality of Tres Lagoas, in Mato Grosso do Sul, Brazil. The original database consisted of 49 soil physicochemical variables collected at 0-0.20 m and 0.20-0.40 m, two dendrometric and four climatic variables, and one response variable related to the height of eucalyptus. A correlation matrix was applied to select variables. Furthermore, modeling was performed using the random forest algorithm, which performed well (r = 0.98, R-2 = 0.96) in predicting the height of eucalyptus. Overall, the most important variables to predict the eucalyptus plant height included diameter at breast height (DBH), phosphorus content (P1), gravimetric moisture (GM1) at a soil depth between 0.00 m and 0.20 m, and exchangeable aluminum content (Al2) between 0.20 m to 0.40 m of soil.
Keywords: Physicochemical variables of soil; machine learning; soil phosphorus content; soil moisture; exchangeable aluminum